2011
DOI: 10.1093/eurheartj/ehr059
|View full text |Cite
|
Sign up to set email alerts
|

Injectable living marrow stromal cell-based autologous tissue engineered heart valves: first experiences with a one-step intervention in primates

Abstract: Here, we provide a novel concept demonstrating that heart valve tissue engineering based on a minimally invasive technique for both cell harvest and valve delivery as a one-step intervention is feasible in non-human primates. This innovative approach may overcome the limitations of contemporary surgical and interventional bioprosthetic heart valve prostheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
114
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(117 citation statements)
references
References 46 publications
3
114
0
Order By: Relevance
“…Despite the encouraging results obtained with preseeded scaffolds in sheep and baboons (Vincentelli et al 2007;Weber et al 2011), the antithrombogenic properties of MSCs (Hashi et al 2007) and their ability to stimulate in vivo endothelialization (Mirza et al 2008) should preclude future requirements for preseeding with endothelial cells.…”
Section: Cell Sources For In Vitro Heart-valve Tissue Engineeringmentioning
confidence: 99%
“…Despite the encouraging results obtained with preseeded scaffolds in sheep and baboons (Vincentelli et al 2007;Weber et al 2011), the antithrombogenic properties of MSCs (Hashi et al 2007) and their ability to stimulate in vivo endothelialization (Mirza et al 2008) should preclude future requirements for preseeding with endothelial cells.…”
Section: Cell Sources For In Vitro Heart-valve Tissue Engineeringmentioning
confidence: 99%
“…However, in vitro endothelialization of grafts involves multiple additional procedures, for instance donation of patient specific tissue for isolation of endothelial cells. In vivo studies showed that implantation of nonendothelialized TEHV resulted in almost confluent endothelialization already after 4-8 weeks in vivo [16,48,50,51]. However, using ADSC for tissue engineering would enable the endothelialization after differentiation of the cells in the presence of vascular endothelial growth factor without requiring any surgical harvesting of additional patientspecific tissues.…”
Section: Discussionmentioning
confidence: 99%
“…A major focus in heart valve tissue engineering is the in vitro creation of mature tissue structures compliant with native valve functionality. Various cell types have been investigated for their suitability for heart valve tissue engineering including high remodeling capacity of the Extracellular Matrix (ECM), including prenatal cells [11][12][13], umbilical cord [14][15][16] and vascular derived cells [17][18][19]. Furthermore the observed multipotency of adult Mesenchymal Stem Cells (MSCs) including their ability to differentiate into cells found in the adult heart, such as cardiomyocytes and endothelial cells, sparked interest to develop them for future cell-based therapy such as heart valve engineering.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[12][13][14] Among various MSC sources, bone marrow-derived MSC (BMMSC) and adiposederived MSC (ADMSC) are prime candidates for TEHV due to their greater availability and popularity. [15][16][17][18][19] However, a few studies have compared phenotype and extracellular matrix (ECM) deposition characteristics between MSC and VIC, especially pediatric VIC. VIC are a heterogeneous population of quiescent fibroblasts, a small population (*20% for neonatal, *6% for child and *2.5% for adult valves) of myofibroblasts and mesenchymal progenitor cells.…”
Section: Introductionmentioning
confidence: 99%